Analysis of mobile learning as an innovation in higher education: a comparative study of three countries. (2017) - Hao, Shuang; Cui, Mengyao; Dennen, Vanessa P.; TÁ¼rel, YalÄ±n KÄ±lÄ±Á§; Mei, Li
This paper examines how mobile learning has been integrated into higher education settings in the USA, China, and Turkey. Mobile learning is a relatively recent innovation, and to date it has largely grown through informal, individual use rather than formal integration in educational settings. This study examines how students perceive mobile learning as an innovation in terms of the following five factors: relative advantage, compatibility, complexity, trialability, and observability. University students in three different countries were surveyed to determine their attitudes towards and beliefs about mobile learning diffusion. The findings show that students are ready for mobile learning, and many students already engage in learning-support activities using their mobile phones on an informal basis. Although mobile learning is currently well-poised for formal learning integration, students have some concerns and needs that should be addressed, including support and infrastructure. Implementation approaches need to consider and reflect cultural differences, which were found across all five dimensions.